The implementation of Islamic management theories in Islamic banks and its implications: A study on encyclopedia of Islamic banks performance evaluation / Mohammad Charif Mohi Mchwh - Mohammad Charif , Mohi Mchwh (2018)
The study aims to reveal the principles, values and foundations out of which the concepts and visions of the theory of Islamic management have been constituted, and define the features and characteristics of this theory and its executive principles to address the issue of deliberate negligence of the existence, role and value of a Sharia-based management theory that compares to and outperforms secular management theories. This research is a qualitative study based on the quantitative results of the Encyclopedia of Islamic Banks Performance Calendar on selected Islamic banks, carried out by the International Institute of Islamic Thought. The research has many findings, most importantly clarifying and framing the theory of Islamic management through revealing the Islamic foundations, values and principles out of which the concepts and visions, forming the theory have been constituted. The research emphasizes the potential of transforming the theoretical propositions of Islamic management theory into executive procedures and demonstrates a lack of practical application of the requirements, values and principles of Islamic management theory in institutions that have adopted the philosophy of Islamic management. The research recommends intensifying research efforts in the field of Islamic management, highlighting its ethical dimension, as well as striving to create contemporary administrative studies which should be capable of providing reasonable solutions based on Sharia and able to fill the gaps in modern management theories.